Development of an immunoFET biosensor for the detection of biotinylated PCR product. Issue 10 (October 2016) - Muangsuwan, Wannaporn; Promptmas, Chamras; Jeamsaksiri, Wutthinan; Bunjongpru, Win; Srisuwan, Awirut; Hruanun, Charndet; Poyai, Amporn; Wongchitrat, Prapimpun; Yasawong, Montri
Abstract: ImmunoFET (IMFET) biosensor is a simple platform for the detection of biotinylated products of polymerase chain reaction (PCR). Construction of the IMFET biosensor started with adsorption of 1.5 mg/mL of protein A (PA) onto the insulated gate surface of ISFET for 90 min. Next, the immobilized 1/500 dilution of anti-biotin antibody was adsorbed onto the PA layer for 60 min. The IMFET biosensor was subsequently ready for detection of the biotinylated amplicon. The IMFET biosensor showed highly specific binding to the biotinylated PCR product of the phaE gene of Haloquadratum walsbyi DSM 16854. The phaE gene is a biomarker of polyhydroxyalkanoate (PHA) producers that contain PHA synthase class III. The lowest amount of DNA template of H. walsbyi DSM 16854 that the IMFET biosensor could detect was 125 fg. The IMFET biosensor has a lower amount of detection compared with a DNA lateral flow biosensor from our previous study. The degree of linearity of the biosensor signal was influenced by the concentration of the biotinylated amplicon. The IMFET biosensor also has a short response time (approximately 30 times) to detect the phaE amplicon compared to an agarose gel electrophoresis. The IMFET biosensor is a promising tool for the detection of the biotinylated PCR product, and it can be integrated into a micro total analysis system (μTAS).